2015
DOI: 10.1007/s12262-015-1213-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the results of total thyroidectomy and Dunhill operation in surgical treatment of multinodular goiter

Abstract: Multi-nodular goiter (MNG) is one of the commonest thyroid gland disease. Surgery is an important treatment option in the presence of indications. There are several alternative procedures for thyroid gland operation such as subtotal thyroidectomy (STT), near-total thyroidectomy (NTT), hemi-thyroidectomy plus subtotal resection (Dunhill procedure), and total thyroidectomy (TT), but the surgical procedure of choice is still under discussion. In this study, 173 consecutive patients with multi-nodular goiter under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…12 Similarly, Mobayen et al in their study found an incidence of 2.8% patients developing seroma after surgery. 17 The major limitations of our study were the small number of cases (n=50), single institutional study and short follow up period.…”
Section: Discussionmentioning
confidence: 90%
“…12 Similarly, Mobayen et al in their study found an incidence of 2.8% patients developing seroma after surgery. 17 The major limitations of our study were the small number of cases (n=50), single institutional study and short follow up period.…”
Section: Discussionmentioning
confidence: 90%
“…This is probably related to a large number of iodine-deficient areas as well as delay in seeking surgical care. 13,14 There was one case of Pendred syndrome where a young female patient had MNG along with bilateral deafness since birth.…”
Section: Discussionmentioning
confidence: 99%
“…Substernal goiter, defined as the positioning of the thyroid tissue under manubriosternal junction, has an incidence of 0.2-4.5% [1]. Recurrent substernal goiter, regeneration of thyroid tissue after thyroid gland surgery, has an incidence of 2.3% [2].…”
Section: Introductionmentioning
confidence: 99%